Investor herds and oil prices evidence in the Gulf Cooperation Council (GCC) equity markets - Talat Ulussever; Rıza Demirer (Central Bank Review (CBR), 2017)
This paper scrutinizes the effect of crude oil prices on herd behavior among investors in the Gulf Cooperation Council (GCC) stock markets. Using firm level data from Saudi Arabia, Qatar, Oman, Kuwait, Bahrain, Dubai and Abu Dhabi stock exchanges, we examine equity return dispersions within industry portfolios and test whether investor herds exist in these markets. We then assess whether crude oil price movements have any effect on the investment behavior of traders in the aforementioned markets. Our findings reveal significant evidence supporting herd behavior in all GCC equity markets with the exception of Oman and Qatar, more consistently during periods of market losses. Furthermore, we find significant oil price effects on herd behavior in these markets, particularly during periods of extreme positive changes in the price of oil. Our findings suggest that investors' tendency to act as a herd in the said markets is significantly affected by the developments in the oil market.
Keywords: G14; G15; 330; Investor herds; Equity return dispersion; GCC stock markets; Crude oil